MATHEMATICAL MODELING OF HEAT WORKING OF THROUGH-TYPE HEATING FURNACES IN SCHEMA OF COUNTER FLOW HEAT EXCHANGE - V. I. Timoshpolskij; M. L. German; I. A. Trusova; P. E. Ratnikov (Литьë и металлургия)
The mathematical model of calculation of metal heating in through-t ype heating and thermal furnaces, using scheme of counter flow heat exchange, is developed.